MASLOW’S HIERARCHY OF NEEDS MANIFESTED BY THE MAIN CHARACTER IN THE FORREST GUMP THE MOVIE - FIEDHAWATIE, SHINTYA DWI (Jurnal Ilmiah Mahasiswa FIB, 2013)
A film is one of  literary works. American film has long been popular with recreating American history. Forrest Gump movie  is chosen to be analyzed in this thesis because it shows the reality and the western historical themes. To support the analysis of the main character, some theories of  the Hierarchy of Needs by Abraham Maslows are utilized to get better understanding about the main character. Since the object of the study is a movie, the researcher also use the movie studies. The  formulated research problem  is on Maslow’s hierarchy of needs manifested  by the main character in  Forrest Gump the movie. The result of this study shows that the Hierarchy of Needs by Abraham Maslow is manifested by Forrest Gump, the main character in this movie. Little Forrest cannot walk properly without braces in his legs, but miraculously he can walk and even run. This kind of way  for being secure, from being bullied, brought him to reach all the impossible things that people think he cannot do. The satisfaction for being loved and belonging with his closest people taught him to face his own destiny. Being rich, famous and having a medal of honor, actually, he did not meant to do it. It is just all about caring, protecting and keeping the people around for being safe and having a comfortable live. Finally, he thought that maybe each people have their own destiny or just live floating around accidental-like on a breeze. At the last, Forrest has his destiny as a “godzilionaire”, a good friend, lovely husband, and a great man as a son and a father.  The other researchers need to do further studies and carry out other pieces of analysis reveal to the important and useful things in  Forrest Gump  the movie. The second possibility is the next researchers may keep using Maslow’s Hierarchy of Needs but they can have different object to analyze or they can use the same movie but different approach.Keywords: Maslow’s hierarchy of needs, self-actualization, Forrest Gump,   Forrest Gump The Movie.